Opening a networked learning dialogue on postdigital citizen science and humanities - Hayes, Sarah; Jandrić, Petar; Tolbert, Sara; Jopling , Michael; Brown , Cheryl (Proceedings of the International Conference on Networked Learning, 2024)
Citizen science, or community science, is generally defined as the involvement of citizens in the collection and analysis of data in collaboration with professional scientists or ecologists. Citizen science initiatives have become more common as technological innovations have increased ways that individuals can participate, enabled larger scale projects and more volunteers to be engaged. Citizen humanities could be said to be a form of citizen science where investigation concerns human values and embedded, diverse, and culturally sensitive knowledge. The development of digital technologies has led to both the field of digital humanities and to new ways to involve citizens in the activities of cultural heritage institutions and academic research. These broad understandings of citizen science and citizen humanities are drawn from disciplinary distinctions concerning how we treat ‘the sciences’ or ‘the humanities’. This is primarily an English language distinction which is much less clear-cut in other languages and cultures, including the ways in which metaphors are adopted as explanatory tools but also carry tacit beliefs and assumptions. In postdigital society it is increasingly hard to separate people’s lives and diverse positionalities from scientific, technological, cultural, linguistic, and political economic changes as these converge to affect communities and individuals. Networked learning is a field that has always shown an active interest in convergences, contribution, and community along with a desire to avoid determinism when examining relationships between learning, technology, and social change. In this paper we draw on this critical networked learning ‘tone’ to explore the activities of citizen science and citizen humanities as they appear to operate as separate fields of research within postdigital society. We argue that discussing the postdigital context surrounding these fields contributes valuable perspectives of knowledge socialism, peer production, collegiality, collaboration, and collective intelligence to help fill certain gaps to meet challenges of the future through community and citizen research. Cross-sector projects that bridge citizen, social, or natural sciences and citizen humanities in diverse locations also need to be community led. This empowers communities not only to acquire new technology enabled capabilities as appropriate to their needs, but also to participate as citizens and activists in the wider political discourse. Therefore, in opening a critically reflexive and relational networked learning dialogue we can locate and occupy important gaps as we grow our understanding of ‘postdigital citizen science’ and ‘postdigital citizen humanities’ as dialectically intertwined fields of cross-sector community research.